Reduction Kinetic of Water Soluble Metal Salts by Geobacter sulfurreducens: Fe2+/Hemes Stabilize and Regulate Electron Flux Rates - Karamash, Maksym; Stumpe, Michael; Dengjel, Jörn; Salgueiro, Carlos A.; Giese, Bernd; Fromm, Katharina M. (Frontiers in Microbiology, 2022)
Geobacter sulfurreducens is a widely applied microorganism for the reduction of toxic metal salts, as an electron source for bioelectrochemical devices, and as a reagent for the synthesis of nanoparticles. In order to understand the influence of metal salts, and of electron transporting, multiheme c-cytochromes on the electron flux during respiration of G. sulfurreducens, the reduction kinetic of Fe3+, Co3+, V5+, Cr6+, and Mn7+ containing complexes were measured. Starting from the resting phase, each G. sulfurreducens cell produced an electron flux of 3.7x105 electrons per second during the respiration process. Reduction rates were within ±30% the same for the 6 different metal salts, and reaction kinetics were of zero order. Decrease of c-cytochrome concentrations by downregulation and mutation demonstrated that c-cytochromes stabilized respiration rates by variation of their redox states. Increasing Fe2+/heme levels increased electron flux rates, and induced respiration flexibility. The kinetic effects parallel electrochemical results of G. sulfurreducens biofilms on electrodes, and might help to optimize bioelectrochemical devices.